Anoctamin 9 determines Ca2+ signals during activation of T-lymphocytes - Schreiber, Rainer; Ousingsawat, Jiraporn; Kunzelmann, Karl (Frontiers in Immunology, 2025)
BackgroundActivation of T-cells is initiated by an increase in intracellular Ca2+, which underlies positive and negative regulation. Because the phospholipid scramblase and ion channel ANO9 (TMEM16J) was shown previously to regulated Ca2+ signals in renal epithelial cells, we asked whether ANO9 demonstrates a similar regulation in T-cells.MethodsWe used measurements of the intracellular Ca2+ concentration to examine the effects of ANO9 on intracellular Ca2+ signaling and demonstrated expression of ANO9 and its effects on cellular and molecular parameters.ResultsANO9 was found to be expressed in human lymphocytes, including the Jurkat T-lymphocyte cell line and mouse lymphocytes. ANO9 has been shown to affect intracellular Ca2+ signals in renal epithelial cells. Here we demonstrate the essential role of ANO9 during initiation of intracellular Ca2+ signals in Jurkat T-cells and isolated mouse lymphocytes. ANO9 is essential for the initial rise in intracellular Ca2+ due to influx of extracellular Ca2+ through store-operated ORAI1 Ca2+ entry channels. ANO9 is indispensable for T-cell function, independent on whether cells are activated by stimulation of the T-cell receptor with CD3-antibody or by PMA/phytohemagglutinin.ConclusionsUpon activation of T-cells and formation of the immunological synapse, ANO9 recruits the Ca2+-ATPase (PMCA) to the plasma membrane, which is supported by the scaffolding protein discs large 1 (DLG1). PMCAs maintain low Ca2+ levels near ORAI1 channels thereby suppressing Ca2+-inhibition of ORAI1 and thus retaining store-operated Ca2+ entry (SOCE). It is suggested that ANO9 has a role in interorganelle communication and regulation of cellular protein trafficking, which probably requires its phospholipid scramblase function.